A Comprehensive Review of Peste Des Petits Ruminants Virus (PPRV) Infection of Small Ruminant and Potential Treatment with Various Plant Extracts - Aruna, C.; Naik, M. Muniya; Mohan, N. Chandra; Reddemma , R.; Kumar, D. Veera Nagendra; Kiran, V. Uday (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Peste des petits ruminants (PPR) is caused by a morbillivirus from the Paramyxoviridae family. PPR is an acute, highly contagious, and deadly disease that mostly affects goats and sheep, with cattle experiencing subclinical infection. The Peste des petits ruminants virus (PPRV) causes the sickness. Given the importance of sheep and goats in the livelihoods of poor and marginal farmers in Africa and South Asia, PPR is a key concern for food security and poverty alleviation. Morbilliviruses PPR virus (PPRV) and render pest virus (RPV) are closely related. This virus can be transmitted from infected animals to vulnerable animals by inhaled aerosols or clinical excretions. PPR symptoms included pyrexia, stomatitis, diarrhoea, ulcerative lesions, and oculo-nasal discharge. This review summarises current advances in PPRV replication, pathology, immunological response to vaccines, and disease control. Attempts have also been made to emphasise current developments in understanding host sensitivity and resistance to PPR, as well as the prevalence of the virus throughout the world and its treatment through the use of various plant materials.